The Relationship Between Emotional Intelligence and Student Leadership at Suryakancana University, Cianjur Scouting Education Program - Apipudin; Asep Ramdan Afriyuandi; Eneng Fitri Amalia (Jumper: Jurnal Mahasiswa Pendidikan Olahraga, 2026)
Thesis Physical Education, Health, and Recreation Study Program, Faculty of Teacher Training and Education, Suryakancana University Cianjur. This study aims to analyze the relationship between emotional intelligence and leadership skills of students participating in the Scouting education program at Suryakancana University, Cianjur. This study is motivated by the importance of strengthening character and soft skills in higher education, particularly through non-formal activities such as Scouting. The method used was a quantitative approach with a descriptive correlational design. The sample consisted of 110 randomly selected students, and data collection was conducted through a questionnaire that met validity and reliability requirements. The results of the correlation test showed a very strong relationship between emotional intelligence and leadership, with a coefficient value of 0.821 and a significance level of 0.000. This finding indicates that the higher the emotional intelligence of students, the better their leadership qualities. This research supports the importance of implementing Scouting education as a strategic tool in developing young leaders with character and emotional competence.